Pengaruh Kepercayaan, Keamanan Dan Kualitas Pelayanan Terhadap Keputusan Pembelian Di Tokopedia - Alim Khoirudin; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of trust, security and service quality on purchasing decisions, the sample of this study is the consumer of the Tokopedia site. To collect data using a questionnaire, to analyze data using validity test, reliability test, normality test, multiple linear analysis, F statistic test and t statistic test, coefficient of determination test in IBM Social Sciences Statistical Package (SPSS) Version 16.0From the results of calculations with SPSS which is a variable of trust, security, service quality have a simultaneous and significant effect on purchasing decisions. While partially the variables of trust, security and service quality have a positive and significant effect on purchasing decisions. Keywords: Trust; Security; Service Quality; Purchasing Decisions